Seroprevalence Study of Influenza Type A of Equidae in Chiangmai and Kanchanaburi Provinces: - - Maneelek, Issaraparb; Lertwatcharasarakul, Preeda; Jala, Siriluk; Laikul, Aree; Punquejana, Weerawat; Cherdchutham, Worakij (Journal of Mahanakorn Veterinary Medicine, 2020)
A seroprevalence survey of Influenza virus type A of Equidae (horse, donkey and mule) was conducted in area of Chiangmai and Kanchanaburi provinces between April to May in 2017. The blood samples collected from total 285 animals, 132 samples from Chiangmai and 153 from Kanchanaburi province, were tested for influenza virus type A antibody by Enzyme-linked immunosorbent assay (ELISA). The mean values of S/N ratio from Equid group age of younger than 1 year old, group 1-2 years old and group older than 2 years old (average 8 years old) were 0.86, 0.85 and 0.86 respectively. The mean values of S/N ratio of Equid from Chiangmai and Kanchanaburi provinces were 0.79 and 0.91 respectively. The S/N ratio value equals or lower than 0.60 was considered positive. In this study, the influenza virus type A antibody was not found from horse, donkey and mule in all age groups of both provinces.